2011
DOI: 10.1007/s00128-011-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Responses of Cyprinus carpio Exposed to a Commercial Formulation Containing Glyphosate

Abstract: The effects of commercial glyphosate herbicide formulation on the activity of acetylcholinesterase (AChE) enzyme and oxidative stress were studied in Cyprinus carpio exposed for 96 h to 0.0, 0.5, 2.5, 5.0 and 10.0 mg/L and then allowed to equal recovery period in water without herbicide. The activity of AChE was inhibited in the brain and in the muscle after exposure. However, after recovery period brain and muscle AChE activity increased. Brain thiobarbituric acid reactive species (TBARS) were measured as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 29 publications
0
44
0
5
Order By: Relevance
“…AChE activity in fish can also be modified by other classes of pesticides, like organochlorines such as endosulfan (Dutta & Arends, 2003). Other authors have also demonstrated the anticholinesterase effect of glyphosate in different fish species (Glusczak et al, 2006;Glusczak et al, 2007;Cattaneo et al, 2011) as well as glyphosate basedproducts, Roundup ® and Roundup Transorb ® on Prochilodus lineatus (Modesto & Martinez, 2010a, 2010b.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…AChE activity in fish can also be modified by other classes of pesticides, like organochlorines such as endosulfan (Dutta & Arends, 2003). Other authors have also demonstrated the anticholinesterase effect of glyphosate in different fish species (Glusczak et al, 2006;Glusczak et al, 2007;Cattaneo et al, 2011) as well as glyphosate basedproducts, Roundup ® and Roundup Transorb ® on Prochilodus lineatus (Modesto & Martinez, 2010a, 2010b.…”
Section: Discussionmentioning
confidence: 95%
“…Ramsdorf et al (2012) also observed an increase in the frequency of Another widely used herbicide in the study area is Roundup ® , a glyphosate based product. The effects of this herbicide on aquatic organisms have been addressed, especially in fish (Glusczak et al, 2006;Cattaneo, 2011;Rossi et al, 2011). Modesto & Martinez (2010a) have shown that this herbicide increases the activity of liver GST and other enzymes involved in antioxidant defense of P. lineatus.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides form the important group of compounds concerning pollution of water bodies. Fish are best indicators of pesticide pollution in an aquatic environment due to the fact that their metabolic state changes frequently in response to pesticides (Begum, 2004;Cattaneo et al, 2011). Various species of freshwater and marine fishes have been used as models for genotoxicity testing in aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Gümüş kedi balığı , Prochilodus lineatus, Leporinus obtusidens, Cyprinus carpio, amfibik kurbağalar, Cnesterodon decemmaculatus türlerine glifosat maruziyeti ile asetilkolin esterazın inhibe olduğu görülmüştür. [58][59][60][61][62][63][64] Glisin ve diğer aminoasitler nörotransmitter olarak görev yapmakla birlikte, beyin fonksiyonları üzerinde önemli rol oynamaktadır. N-fosfonometil glisin yapısında bir herbisit olan glifosatın, glisin tü-ketimine neden olarak hücre proliferasyonunu inhibe ettiği düşünülmektedir.…”
Section: Si̇ni̇r Si̇stemi̇ üZeri̇ne Etki̇leri̇unclassified